Effect of inner retinal dysfunction on slow double-stimulation multifocal electroretinogram. Issue 11 (17th August 2011) - Chu, Patrick H W; Ng, Yiu-Fai; Ting, Patrick W K; Lung, Jenny C Y; Ho, Wing-Cheung; So, Kwok-Fai; To, Chi-Ho; Chan, Henry H L
Abstract : Purpose: This study investigated the retinal adaptive mechanism in inner retinal dysfunction using the slow double-stimulation multifocal electroretinogram (mfERG) paradigm. Methods: Slow double-stimulation mfERG responses were recorded from 15 eyes of 15 4-month-old Mongolian gerbils in control conditions and after suppression of inner retinal responses with injections of tetrodotoxin (TTX) and N -methyl-d -aspartic acid (NMDA). The stimulation consisted of five video frames: the two initial frames with multifocal flashes were triggered by two independent m-sequences, followed by three dark video frames. The results were compared with findings in humans: 7 subjects with glaucoma and 31 age-matched normal subjects were measured using the same mfERG protocol. Results: The stimulation generates two responses (M 1 and M 2 ) from the two independent multifocal frames. The M 1 :M 2 ratio showed a significant reduction after administration of TTX+NMDA in the animal study. This matched with the human glaucoma findings. Glaucoma subjects generally have a reduced M 1 :M 2 ratio; this ratio showed a sensitivity of 86%, with a specificity of 84% for differentiating normal eyes from glaucomatous eyes. Conclusion: This stimulation paradigm provides a method of measuring temporal visual characteristics. The M 1 :M 2 ratio acts as an indirect functional indicator of retinal adaptation, which may be abnormal in the diseased retina. Further development of this method may help to describe the functional variation in the diseased retina and to predict the occurrence of a range of retinopathies.